Nitric oxide synthase and NAD(P)H oxidase modulate coronary endothelial cell growth - Bayraktutan, Ulvi (2004)
Reactive oxygen species (ROS) including nitric oxide (NO) and superoxide anion (O2-) are associated with cell migration, proliferation and many growth-related diseases. The objective of this study was to determine whether there was a reciprocal relationship between rat coronary microvascular endothelial cell (CMEC) growth and activity/expressions (mRNA and protein) of endothelial NO synthase (eNOS) and NAD(P)H oxidase enzymes. Proliferating namely, 50% confluent CMEC possessed approximately three-fold increased activity and expression of both enzymes compared to 100% confluent cells. Treatment of CMEC with an inhibitor of eNOS (L-NAME, 100M) increased cell proliferation as assessed via three independent methods i.e. cell counting, determination of total cellular protein levels and [3H]thymidine incorporation.